2008
DOI: 10.1002/jcla.20261
|View full text |Cite
|
Sign up to set email alerts
|

RNA from Borna disease virus in patients with schizophrenia, schizoaffective patients, and in their biological relatives

Abstract: Numerous interactions of the immune system with the central nervous system have been described recently. Mood and psychotic disorders, such as severe depression and schizophrenia, are both heterogeneous disorders regarding clinical symptomatology, the acuity of symptoms, the clinical course, the treatment response, and probably also the etiology. Detection of p24 RNA from Borna disease virus (BDV) by the reverse transcriptase polymerase chain reaction in patients with schizophrenia, schizoaffective disorder, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…The detection of BDV‐RNA in peripheral blood of psychiatric patients and their relatives using ultrasensitive reverse transcription–polymerase chain reaction 9–11 further supported this hypothesis, although sequence similarities between human BDV strains and laboratory strains highlighted the possibility of false‐positive results due to contaminations, 12,13 and the importance of rigorous safety conditions. A triple enzyme‐linked immunosorbent assay (ELISA) developed by Bode et al.…”
supporting
confidence: 52%
“…The detection of BDV‐RNA in peripheral blood of psychiatric patients and their relatives using ultrasensitive reverse transcription–polymerase chain reaction 9–11 further supported this hypothesis, although sequence similarities between human BDV strains and laboratory strains highlighted the possibility of false‐positive results due to contaminations, 12,13 and the importance of rigorous safety conditions. A triple enzyme‐linked immunosorbent assay (ELISA) developed by Bode et al.…”
supporting
confidence: 52%
“…It has been reported that BDV is not associated with psychiatric patients in Kyushu island in Japan, a known endemic area of BDV infection 8,42,49. However, there have been two BDV-positive reports in Brazil, which has not been known to be an endemic BDV infection area 23,24. Third, the pathogenesis and symptoms of BDV infection in humans would be different from the infection in animals.…”
Section: Discussionmentioning
confidence: 95%
“…Borna disease virus RNA positivity was detected in patients with psychotic disorders (44.4%), relatives without mental disorders (50%), relatives with mental disorders (37.5%) and healthy controls (14.8%) [25]. …”
Section: Discussionmentioning
confidence: 99%